2023
DOI: 10.1186/s13098-023-01085-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SGLT-2 inhibitors on adipose tissue distribution in patients with type 2 diabetes mellitus: a systematic review and meta-analysis of randomized controlled trials

Abstract: Objective Sodium-glucose cotransporter-2 (SGLT-2) inhibitors therapies were reported to affect adipose tissue distribution. However, the available evidence about the effect of SGLT-2 inhibitor on adipose tissue is contradictory. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effect of SGLT-2 inhibitors on adipose tissue distribution in patients with type 2 diabetes mellitus (T2DM). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…SGLT2 inhibitors may offer advantages to patients with diabetic NAFLD due to their known ability to induce weight loss and lower glucose . SGLT2 inhibitors redistribute visceral, subcutaneous, and ectopic fat (eg, liver fat) depots . SGLT2 inhibitors facilitate glucose loss through the kidney, which provokes a fastinglike state and activates catabolic pathways in the liver and visceral adipose tissues .…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors may offer advantages to patients with diabetic NAFLD due to their known ability to induce weight loss and lower glucose . SGLT2 inhibitors redistribute visceral, subcutaneous, and ectopic fat (eg, liver fat) depots . SGLT2 inhibitors facilitate glucose loss through the kidney, which provokes a fastinglike state and activates catabolic pathways in the liver and visceral adipose tissues .…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, four types of interventions have been proposed to reduce EAT volume, including exercise interventions, dietary interventions, bariatric surgery, and pharmaceutical interventions 129–134 (Figure 3). There have been a number of well‐designed tables summarizing related clinical studies in recent systematic reviews 134–142 …”
Section: Exploration Of Targeting Eat As a Therapeutic Strategymentioning
confidence: 99%
“…Clinical evidence demonstrated that the SGLT-2I could exert progressive BMI reduction at 12 (MD = − 0.52 kg/m 2 ), 24 (MD = − 0.73 kg/m 2 ), 52 (− 0.93 kg/m 2 ), and 104 (− 1.22 kg/m 2 ) weeks [ 59 ]. Further body composition studies showed that within the duration of treatment, lean body mass remained stable [ 64 ], while fat depletion in subcutaneous, visceral, and liver/ectopic sites were all significant [ 65 ]. Specifically, the SGLT-2I could deplete liver fat via glucose deprivation (as de novo lipogenesis accounts for one-fourth of hepatic FA content in MASLD) [ 66 ] and glucose deprivation-boosted hepatic FA β-oxidation.…”
Section: Sodium-glucose Cotransporter-2 Inhibitor (Sglt-2i)mentioning
confidence: 99%
“…The SCD2023 recommends that a SGLT-2I should be included in the treatment regimen for patients with T2DM and established cardiovascular/renal disease or risks [ 67 ], as the major CVOTs indicated that risks of MACE (HR = 0.89) and cardiovascular death or hospitalization for heart failure (HR = 0.77) were all significantly reduced in patients with T2DM receiving SGLT-2I treatment [ 68 ••], though the SGLT-2I is associated with a statistically but not clinically significant increase in total plasma cholesterol (MD = 0.003 mmol/L) [ 69 ] and an insignificant depletion in epicardial fat [ 65 ]. Moreover, a pooled analysis of 31 RCT (including all up-to-date CVOT) demonstrated that compared with placebo or no therapy, the SGLT-2I could also significantly reduce the incidence of total (risk ratio (RR) = 0.83) and serious (RR = 0.75) atrial fibrillation [ 70 ].…”
Section: Sodium-glucose Cotransporter-2 Inhibitor (Sglt-2i)mentioning
confidence: 99%